Glucose metabolism reprogramming promotes immune escape of hepatocellular carcinoma cells - Qiuyue Zhang; Jinchen Liu; Haifeng Lin; Bo Lin; Mingyue Zhu; Mengsen Li (Open Exploration Publishing Inc., 2023)
Hepatocellular carcinoma (HCC) is a complex process that plays an important role in its progression. Abnormal glucose metabolism in HCC cells can meet the nutrients required for the occurrence and development of liver cancer, better adapt to changes in the surrounding microenvironment, and escape the attack of the immune system on the tumor. There is a close relationship between reprogramming of glucose metabolism and immune escape. This article reviews the current status and progress of glucose metabolism reprogramming in promoting immune escape in liver cancer, aiming to provide new strategies for clinical immunotherapy of liver cancer.